CEREBROPROTECTIVE POTENTIAL OF TRANSPLANTATION OF RAT EMBRYONIC FIBROBLASTS IN THE TREATMENT OF EXPERIMENTAL ACUTE ISCHEMIC STROKE - Konovalov, Serhii; Moroz, Vasyl; Yoltukhivskyi, Mykhaylo; Gadzhula, Nataliia; Cherepakha, Olena (Eastern Ukrainian Medical Journal, 2026)
Introduction. Currently, ischemic stroke is one of the most common neurological diseases, characterized by high mortality and disability rates. Stem cell-based therapies, particularly embryonic stem cells, is a promising direction in the modern treatment of ischemic stroke.Objective: To evaluate the cerebroprotective effect of rat embryonic fibroblast transplantation in acute ischemic stroke.Methods. The study was conducted on 74 Wistar rats using a model of transient bilateral 20-minute ischemia-reperfusion by bilaterally ligating the internal carotid arteries. The animals were divided into three research groups: 1 – sham-operated animals, 2 – a control pathology group (intravenous injection of 0.9% NaCl solution post-ischemia-reperfusion), and 3 – a treatment group (intravenous transplantation of rat embryonic fibroblasts at a dose of 106 cells per animal, suspended in 0.2 ml of physiological saline post-ischemia-reperfusion). The effects of fibroblast transplantation were assessed based on mortality rates and neurological deficit dynamics using the McGraw Stroke-index. Hippocampal damage in the rats’ brains was evaluated immunohistochemically using specific anti-NeuN antibody markers, while DNA fragmentation in hippocampal neuron nuclei was measured via flow cytometry.Results. The obtained results showed that with subtotal cerebral ischemia (bilateral occlusion of the internal carotid arteries) in rats, first of all, significant neurodegenerative processes occur in the dentate gyrus in the CA1 area, and this leads to significant disturbances in the neurological status of the experimental animals and their high lethality. Therapy by intravenous transplantation of rat embryonic fibroblasts significantly reduced mortality rates, improved neurological status, and decreased neuroapoptosis in the hippocampus. Additionally, NeuN-positive neuron fluorescence intensity in the CA1 hippocampal region increased more than twofold compared to the control pathology group.Conclusions. Experimental therapy with intravenous transplantation of rat embryonic fibroblasts preserved cytoarchitectonic integrity in the pyramidal layer of the CA1 hippocampal region and significantly reduces the level of DNA fragmentation in hippocampal neuron nuclei. These effects, along with decreased mortality rates and improved neurological outcomes, highlight the neuroprotective potential of embryonic fibroblasts in ischemic stroke. These findings indicate the promising use of embryonic fibroblasts for neuroprotection in ischemic stroke, which may provide a foundation for further research in this field.